L’univers esthétique des photographies de Cy Twombly et le renouvellement du regard sur son œuvre - Chiara Agradi (Les Cahiers de l'École du Louvre)
Cy Twombly’s photographic oeuvre includes a huge number of Polaroids, printed using the dry-print technique and Fresson process. More than just a photographer, Twombly is an art theoretician who examines the interactions between painting and photography. Through his manipulation of the material, he questions the limits of the photographic object and disrupts the world of the instant photograph, which he transforms into a unique, hybrid object. The ceiling painted by the artist in the room of Greek and Roman antiquities in the Louvre bears witness to his interest in the dialogue between photography, painting and American culture, and was consistent with his aesthetic experiments, particularly regarding his fascination for Mediterranean culture. Far from being simply decorative, the Louvre ceiling could be interpreted as a large photograph, a fugitive piece of reality captured and circumscribed in the space of a limited frame.